Volunteerism is Associated with Improved Student Soft Skills: A Case Study in a Marine Engineering Program in the Philippines - Llenares, Ian I.; Deocaris, Custer (Journal of Interdisciplinary Studies in Education, 2019)
In this study, we assessed student soft-skills after a 36-month long community service program in a Philippine private higher education institution. The Soft Skills-Graduate Attribute Scale was developed to measure professional competence, critical thinking skills, communication skills, lifelong learning, social and ethical responsibility, productivity, and interpersonal skills. Sixty (60) marine engineering students were purposively selected based on their participation in the various community service activities. The result shows that students who regularly volunteered have significantly higher measures of graduate attributes relating to professional competence, communication skills, and social and ethical responsibility as compared to non-regular and first-time volunteers. This study underscores the value of service learning programs in higher education in improving soft skills as well as the cross-cultural competencies of students in highly technical fields.